MENYOAL KEMBALI PERKAWINAN DI BAWAH TANGAN (NIKAH SIRRI) DI INDONESIA - Abdullah, Nafilah (Sunan Kalijaga State Islamic University & The Asia Foundation, 2013)
All people who enter the gates of family life through marriages intend to achieve aÂ prosperous and harmonious family life and receive blessing in this world and the next. Marriages must therefore be done in accordance with religious law. A marriage is legal if conducted in accordance with oneâ€™s religion, and must be recorded in the Office of Religious Affairs (KUA). Marriages which are not recorded by authorized officials are sirri marriages, and are contrary to legislation. Furthermore, its harm can be seen from its consequence, the lack of legal certainty between husband and wife and the children. This entails the legal consequence that sirri marriages do not have a Marital Deed and children borne of such marriage receive no government recognition, and are considered children born out of wedlock, only having civil relations with the mother and the motherâ€™s family. The wife and children abandoned by a biological father cannot take legal action for the fulfillment of their economic rights or for joint marital assets.